xy(a^2+b^2)-ab (x^2+y^2)
Answers
Answered by
5
hope it helps you.
mark as brainliest please
mark as brainliest please
Attachments:
![](https://hi-static.z-dn.net/files/d1b/6c21bc2baef1eb9397b2683733594c3e.jpg)
anam76233:
its a wrong answer
Answered by
3
Hey here is your answer
=xya^2+xyb^2-abx^2-aby^2
=(xya^2-abx^2)+(xyb^2-aby^2)
=ax(ya-bx)+by(xb-ay)
=xya^2+xyb^2-abx^2-aby^2
=(xya^2-abx^2)+(xyb^2-aby^2)
=ax(ya-bx)+by(xb-ay)
Similar questions
English,
8 months ago
Chemistry,
8 months ago
English,
8 months ago
Economy,
1 year ago
Social Sciences,
1 year ago
Social Sciences,
1 year ago